2005
DOI: 10.2527/2005.8392189x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium chloride, zinc chloride, and water infusion on metmyoglobin reducing activity and fresh lamb color

Abstract: Calcium chloride (CaCl2), zinc chloride (ZnCl2), or water infusions were used to investigate the biochemical factors that affect fresh lamb color, and to examine the role of metmyoglobin-reducing activity in regulating this important quality attribute. Immediately after exsanguination, lamb carcasses (n = 6 per treatment) were infused (10% of BW) with 0.3 M CaCl2, 0.05 M ZnCl2, or water via a catheter inserted into the left carotid artery. The right LM was excised at 24-h postmortem and divided into two halves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 65 publications
0
6
0
2
Order By: Relevance
“…The presence of several muscle compounds such as anserine, carnosine, lactate, NADH, and others (Table ) have been shown to have various physiological roles including antioxidant activity (Halliwell ; Faustman and others ). However, their role in postmortem muscle is controversial due to changes in muscle pH that can affect the activity of the compounds (as for carnosine) (Bekhit and others ; ), and hasten the depletion of others (such as NADH and NADPH) (Bekhit and others ).…”
Section: Other Endogenous Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of several muscle compounds such as anserine, carnosine, lactate, NADH, and others (Table ) have been shown to have various physiological roles including antioxidant activity (Halliwell ; Faustman and others ). However, their role in postmortem muscle is controversial due to changes in muscle pH that can affect the activity of the compounds (as for carnosine) (Bekhit and others ; ), and hasten the depletion of others (such as NADH and NADPH) (Bekhit and others ).…”
Section: Other Endogenous Antioxidantsmentioning
confidence: 99%
“…Lee and Hendricks () found that the pH range of a meat homogenate should be 7.0 to 8.0 for carnosine to exert antioxidant activity. Carnosine was not effective in protecting beef patties from oxidation (Bekhit and others , ) and was not capable of delaying the lipid oxidation in liposomes and an oxygen model system, even at a concentration of 100‐fold the effective Trolox concentration (Jongberg and others ). Therefore, carnosine is unlikely to exert any protective function in meat.…”
Section: Other Endogenous Antioxidantsmentioning
confidence: 99%
“…However, there are several side effects with calcium chloride treatments. For example, they cause meat discoloration (Bekhit et al, 2005) and generate bitter and metabolic off-flavors (Morgan, Miller, Mendez, Hale, & Savell, 1991). In contrast, the traditional plant protease treatments remain a viable option for meat tenderization today.…”
Section: Introductionmentioning
confidence: 98%
“…Although CaCl 2 has proven effective on meat tenderness, there are certain negative effects on the meat quality as well. It impairs the color stability by inducing discoloration and reduces oxidative stability, water‐holding capacity, and product shelf‐life (Bekhit et al., ; Bunmee, Jaturasitha, Kreuzer, & Wicke, ; Kerth, Miller, & Ramsey, ; Jaturasitha, Thirawong, Leangwunta, & Kreuzer, ). Gerelt, Ikeuchib, Nishiumic, and Suzuki () reported that dipping of meat in 150 mM calcium chloride solution after osmotic dehydration can be used to improve tenderness without adversely affecting other palatability and quality traits.…”
Section: Introductionmentioning
confidence: 99%